Influence of Foot Massage and Soak Warm Water Feet Against The Edema of Trimester III Pregnant’s Woman Leg In Tamansari Public Health Center Tasikmalaya Town - Nurma Nisa Aulia; Siti Saadah; Sariestya Rismawati (Midwifery and Nursing Research, 2020)
Background : Leg Edema or swelling of the legs found approximately (80%) In the trimester III of pregnant women. Leg Edema or swelling of the legs is one of the many discomfort found in the trimester III  pregnant women, resulting from the blood circulation in the leg. Complementary therapies that can be done to reduce foot edema with foot massage and soak warm water feet. This research aims to determine the influence of foot massage and soak feet with warm water against the edema of trimester III pregnant’s woman leg.Methods : This research uses pre-experimental methods with the design of one group pre-test and post-test. Population of this research is the trimester III of pregnant women with physiological foot edema in Tamansari Public Health Centre area of 620 people, while the samples used as many as 31 people using purposive sampling technique. Test statistics using Wilcoxon test.Results : The results showed from 31 respondents before the intervention of most edema levels in the 1st degree as much as 21 people (67.7%) and after the intervention of most levels of edema in degrees 0 as much as 20 people (64.5%). Results of data analysis using Wilcoxon test obtained p value = 0.000, because the value of P value 0.000 0.05 which means there is influence of foot massage and soak the feet with warm water against the edema of trimester III pregnant's woman leg.Conclusion : Midwives need to intervene foot massage and soak warm water feet to the trimester III pregnant women.